Chronic myeloid leukemia in the elderly: long-term results from randomized trials with interferon α - Berger, Ute; Engelich, G.; Maywald, O.; Pfirrmann, M.; Hochhaus, Andreas; Reiter, Andreas; Metzgeroth, Georgia; Gnad-Vogt, Ulrike; Hasford, J.; Heinze, B.; Heimpel, H.; Hossfeld, D. K.; et al. (Leukemia, 2003)
Chronic myeloid leukemia (CML) in older patients has not been studied well. To assess the long-term outcome of older patients with Philadelphia- and/or BCR-ABL-positive CML, 199 patients aged ⩾60 years representing 23% of 856 patients enrolled in the German randomized CML-studies I (interferon α (IFN) vs hydroxyurea (HU) vs busulfan (BU) and II (IFN+HU vs HU alone) were analyzed after a median observation time of 7 years. In all, 45 patients were treated with Bu, 63 with HU, and 91 with IFN. The 5-year survival was 38% in patients ⩾60 years and 47% in patients <60 years (P<0.001). Whereas 5-year survival in chemotherapy-treated older patients was inferior to that in younger patients (33 vs 46%, P=0.006 for HU and 29 vs 38%, P=0.042 for Bu), no significant survival difference could be verified in IFN-treated patients (46 vs 53%, P=0.077). Calculation of age-adjusted, relative survival confirmed these results. Adverse effects of IFN were similar in both age groups, but IFN dosage to achieve treatment goals was lower in older patients. We conclude that the course of CML is not different in the elderly. They require lower IFN doses, achieve the same hematologic and cytogenetic response rates and the same survival advantage at comparable toxicity.
Gesehen am 13.05.2022